Matrix Characteristics Influence on Mechanical Performance of Oil Palm Filler Reinforced Nanocomposite - Wong, Hwan Liang Dominick (Curtin University, 2022)
In this research, degassing processes, sonication parameter, influence of nanofillers properties, and densities of the matrix were investigated. It was found that 0.3125 wt% OPEFB filler and 0.25 wt% spherical-shaped nanoparticles resulted in a nanocomposite with good dispersion and effective tensile strength. Through qualitative and quantitative analysis, it was also discovered that the matrix density greatly influences the interfacial bonding between filler and matrix. Such findings would facilitate the development of effective matrix-based nanocomposite materials.